2014
DOI: 10.1182/blood.v124.21.5314.5314
|View full text |Cite
|
Sign up to set email alerts
|

High IDH1 Expression Is Associated with a Poor Prognosis in Cytogenetically Normal Acute Myeloid Leukemia

Abstract: The prognostic value of IDH1 mutations has been systematically evaluated in acute myeloid leukemia (AML) patients recently. However, the role of IDH1 expression in AML is still under exploration. To investigate the clinical significance, we analyzed the IDH1 expression in 320 patients with cytogenetically normal AML (CN-AML) by quantitative real-time reverse-transcription polymerase chain reaction (qRT-PCR). High expression of IDH1 was predominant in patients with FLT3-ITD and DNMT3A mutations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 0 publications
0
19
1
Order By: Relevance
“…In the normal karyotype group, frequency of IDH mutations was even higher with 47.6% of the patients being positive. Other authors reported higher frequency of IDH mutations in the group of AML patients with normal karyotype than when cytogenetic analysis was not taken into consideration (Marcucci et al reported 33%, [24] Emadi et al reported 25%, [25] Ma et al reported 21.56%) [26] but still the frequencies reported in their studies were less than that detected in our study.…”
Section: Discussioncontrasting
confidence: 77%
“…In the normal karyotype group, frequency of IDH mutations was even higher with 47.6% of the patients being positive. Other authors reported higher frequency of IDH mutations in the group of AML patients with normal karyotype than when cytogenetic analysis was not taken into consideration (Marcucci et al reported 33%, [24] Emadi et al reported 25%, [25] Ma et al reported 21.56%) [26] but still the frequencies reported in their studies were less than that detected in our study.…”
Section: Discussioncontrasting
confidence: 77%
“…DNA and RNA samples obtained from mononuclear cells from BM samples at primary diagnosis were extracted as described previously [ 9 ]. Mutation analyses of NPM1, FLT3-ITD, CEBPA, DNMT3A, IDH1 and IDH2 were carried out as described previously [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
“…For example, low expression of the brain and acute leukemia cytoplasmic (BAALC) and ETS-related gene (ERG) genes have been associated with better outcome in CN-AML patients [ 7 , 8 ]. Recently, we found that high expression of HIP1 and IDH1 were associated with poor survival in AML [ 9 ]. In addition to genetic alterations in protein coding genes, aberrant expression of noncoding RNAs might play an important role in leukemia initiation and outcome prediction [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…10 Mutation analyses of NPM1, FLT3-ITD, CEBPA, DNMT3A, IDH1 and IDH2 were carried out as described previously. 10…”
Section: Cytogenetic and Gene Mutation Analysismentioning
confidence: 99%